المواءمة الشرعية والرقابة والتنظيم للصناعة المالية الإسلامية: تجربة البنك المركزي المالزي = Shari`ah harmonisation and regulatory consolidation: BNM experience - Engku Ali, Engku Rabiah Adawiah (2013)
It is important that the legal and regulatory framework of the country that has Islamic banking and finance operations recognizes and addresses the differences between Islamic finance and its conventional counterpart properly so as to prevent inappropriate regulation and regulatory arbitrage. In the past or perhaps even in the present time, this aspect of concern has not been addressed adequately. This paper attempts to highlight the main issues and conflicts that occur between the legal framework and the Shariah requirements of Islamic banking transactions; and the Malaysian experience, in particular, that of the Central Bank of Malaysia (BNM), in trying to harmonize the legal framework with the Shariah, to facilitate better implementation & Shariah compliance of Islamic banking & finance in the country.